Culture as an Unsolved Problem in ELT Program in Post-Revolutionary Iran: A Comparative Survey of the Attitudes of Teachers at Schools and Language Institutes - Hossein Davari; Abutaleb Iranmehr (Comparative Education Society of Iran ( CESIR), 2021)
While for decades learning English has mostly been accompanied by learning its culture, in recent two decades due to the presence of some critical trends in the field of applied linguistics, the mere integration of target culture in English textbooks has been challenged. Not surprisingly, following this shift, the idea of integrating source culture in English textbooks has caught the researchers' attention. Since the cultural content of English textbooks used in schools and language institutes in Post-revolutionary Iran has always been a controversial issue, in this paper, through a qualitative study, it was attempted to comparatively study the attitudes of Iranian language teachers at schools and language institutes as two contrasting contexts about the issue. In doing so, the attitudes of twenty five teachers in these two sectors, including thirteen school teachers and twelve language institute teachers, selected through convenience sampling, surveyed through semi-structured interviews. Findings revealed that while there were some partial differences in the attitudes of these two groups toward the concept of culture and its representation in textbooks, due to the dominance of the mainstream ELT, known as the liberalist approach, that publicizes the inclusion of target culture and rejects the integration of local culture in English textbooks as well as the failure of English education in schools, the participants were mostly in favor of integrating target culture as an indispensable part of English textbooks. These findings may have pedagogical implications for language policy makers, syllabus designers and textbook developers.